The *SAT I for dummies - Woods, Geraldine (Wiley Pub., 2006)
Completely revised to cover the new test! Everything you need to know to score your best . . . Covers math, critical reading, and writing in one complete practice test . . . Tips and techniques for the essay section of the test . . . . Covers the new writing section and expanded math. This easy-to-follow guide arms you with tons of practice questions, detailed answers, and plenty of savvy test-taking techniques, as well as a practice exam. From reading comprehension and sentence completion to math and grammar essentials, you'll be fully prepped to take on the new exam and score your best. Geraldine Woods has more than 25 years of teaching experience. She currently teaches English and directs the independent study program at a high school for gifted students.